Brilliant NLP workbook - Molden, David; Hutchinson, Pat (Prentice Hall Business, 2012)
NLP is a powerful set of tools for making things happen for you at work and in life. Now Brilliant NLP makes mastering the techniques of NLP easy how it works, and more importantly how to use it to become more effective, efficient, powerful and successful. The potential is already there, inside you. This book shows you how to unleash it on the world! New to the edition: Revisions through-out and more examples, research and statistics Two new chapters: 1. 'Why you buy stuff you don't need' reveals how the big brands such as Coca Cola and Nike use NLP techniques to sell you their products. 2. 'You and your personal reality tunnel' helps the reader consider how their 'personal reality tunnel'. i.e. what we consider right and proper and what we accept from society, acts as a limitation on their life.